Production of Polyhvdroxyalkanoates from Synthetic Wastewater Using Sequencing Batch Reactors in On-Off Sequences - Tjandra Setiadi; herriyanto Ronny Sondjaja; Bambang Veeriansyah (ASEAN Journal of Chemical Engineering, 2004)
The biosynthesis of polyhydroxyalkanoates (PHAs) using activated sludge as cultureorganism from tapioca synthetic wastewater has been studied in a 6L sequencing batch reactor (SBR). It was found that longer aeration time caused greater chemical oxygen demand (COD) reduction but did not achieve the maximum PHA-production rate. The application of on-off sequences, however, gave an acceptable PHA- productivity rate at 0.1033 gPHA L-1 h-1 and a high storage yield of up to 0.32 gPHNg biomass, although it caused a decrease in pH and affected sludge stability. The on-off variation also produced a higher valerate copolymer content, in the range of 16.44-22.48 % for Run 1 and of 13.09-14.09 % for Run 2, compared to the customary aerated-unaerated variations. The study indicates that the use of on-off SBR sequences may be suitable for obtaining high PHA-storage yields.